Marking a century of the Department of chemistry and biochemistry at School of medicine in Zagreb honoring professors Tomislav Pinter and Mihovil Proštenik as Fran Bubanović’s successors - Mlinac Jerković, Kristina; Damjanović, Vladimir; Kalanj Bognar, Svjetlana; Lovrić, Jasna (2019)
In 2018 the Department of Chemistry and Biochemistry at Zagreb School of Medicine celebrated 100 years since it was established by professor Fran Bubanović. This essay is focused on his successors, outstanding teachers and scientists, professors Tomislav Pinter and Mihovil Proštenik, members of Yugoslavian (today Croatian) Academy of Sciences and Arts. Tomislav Pinter was a prominent physical chemist who had an original approach and gave novel interpretation of van der Waals and Wohl’s equations. He also served as the president of Croatian Chemical Society. Neurobiochemist Mihovil Proštenik started as an organic chemist at “Prelog’s Zagreb School of Organic Chemistry”. He collaborated with two Croatian Nobel prize winners in chemistry: his PhD thesis supervisor Vladimir Prelog and Lavoslav Ružička. He was the founder of “Zagreb School of Lipidology”, discovered a new sphingoid base C20-sphingosine, and had a major role in the establishment of Ruđer Bošković Institute. Herein we honor their contributions to Croatian science and beyond, and share so far unpublished valuable material from the Department archive.
Bibliografija: 42 jed.
Abstract.
Keywords: Medicinska kemija -- Medicinska biokemija -- Fizikalna kemija -- Lipidi -- Sfingolipidi -- Sfingozin; Bubanović, Fran -- Prelog, Vladimir -- Ružička, Lavoslav -- Pinter, Tomislav -- Proštenik, Mihovil; Medicinski fakultet Sveučilišta u Zagrebu -- Zagrebačka škola lipidologije -- Hrvatska akademija znanosti i umjetnosti -- Institut Ruđer Bošković u Zagrebu; 20. st; Hrvatska -- Zagreb